2018
DOI: 10.1080/03054985.2018.1450745
|View full text |Cite
|
Sign up to set email alerts
|

Neither a borrower nor a lender be: exploring ‘teaching for mastery’ policy borrowing

Abstract: This paper examines an instance of policy borrowing, specifically, the borrowing of 'mathematics mastery'. In doing so, it considers some of the implications of parachuting policy from one setting into another. The process of borrowing mastery is examined not only as a policy technology, but also as a culturally located artefact embedded in the 'high performing' education systems of Shanghai and Singapore. Drawing on empirical evidence, the paper maps how teachers working in the East Midlands region of England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…It is unsurprising, therefore, that East Asian mathematics education policies and practices have attracted considerable interest from education policymakers in England. The PISA mathematics performance of East Asian regions has been a significant factor in motivating English policymakers to 'borrow' mathematics education policies from these high performing jurisdictions (Clapham & Vickers, 2018).…”
Section: Policy-borrowing In Mathematics Education: the Situation In mentioning
confidence: 99%
See 4 more Smart Citations
“…It is unsurprising, therefore, that East Asian mathematics education policies and practices have attracted considerable interest from education policymakers in England. The PISA mathematics performance of East Asian regions has been a significant factor in motivating English policymakers to 'borrow' mathematics education policies from these high performing jurisdictions (Clapham & Vickers, 2018).…”
Section: Policy-borrowing In Mathematics Education: the Situation In mentioning
confidence: 99%
“…Whilst the aims of mastery teaching are very laudable, its operationalisation in England conflicted with significant aspects of the prevailing sociocultural context. For example, primary mathematics is taught by subject specialists in East Asian regions but by generalists in England, and this is further exacerbated by significant differences in the structures of the school day and attitudes to using textbook-based exercises between England and East Asian jurisdictions (Clapham & Vickers, 2018). Furthermore, Clapham and Vickers (2018) suggested that the implementation of mastery teaching in England was compromised by differences between the learning cultures of England and East Asia, in terms of the 7 commitment and work ethic of students.…”
Section: (Department For Education 2016)mentioning
confidence: 99%
See 3 more Smart Citations